انتفاضة و مجازر 8 ماي 1945م في منطقة سطيف: بلدية تاقيطونت المختلطة نموذجا (محـاولة في التاريخ المحـلي) (El-Wahat Journal for Research and Studies, 2015)
The Insurrection and the massacres of 8 May 1945 in the area of Setif: mixed commune of Takitount as a model (essay in the local history), in the Arabic language.     This study is a modest contribution for the writing of the local history of some areas of the dear Algerian country.  We have selected a region located in the state of Setif and specifically in the northern east part, which was during the French colonialism an administrative unit designed mixed commune of Takitount.     We applied this new approach to write our national history in the mentioned region with a specific theme which deals with the causes of the uprising of the Algerians against the colonial authorities on 8 May 1945, and the subsequent massacres committed by the French. Our goal was to collect new data, never published in previous studies based on the classical methodology which deals with the causes of the insurrection in general.      Despite the multiplicity and diversity of reasons, this study finds that the main reason of the insurrection and the terrible massacres is a psychological factor: the abhorrent racism expressed by the intruder community (European settlers) toward the inherent community land owner (Algerians), then comes the other factors. These events caused the irreversible estrangement between the two communities which led to the revolution of first November 1954 and later on the glorious independence in 1962.